Measurement and Characteristic Analysis of Electromagnetic Disturbance of Coal Mine Fan Converter. (5th August 2021) - Xin, Zhonghua; Zhang, Xiaodong; Yu, Shuqian; Wang, Huijuan; Jia, Xiaoqian; Ma, Yuling
Abstract : With the extensive use of converters in high-power ventilator, shearer, road header, conveyor, hoist, and other coal mine equipment, the electromagnetic disturbance problem of the converter is worthy of attention. In this paper, the field measurement and statistical method are used to analyze the radiation interference characteristics of frequency converter. Then, a typical fan converter is taken as an example, and the electromagnetic disturbance of the converter is tested in four key positions and two working frequencies, respectively. Multiple sets of data and spectrum are obtained by using a spectrum analyzer and other instruments, and the dominant frequency characteristic parameters of the converter are analyzed emphatically. The small sample data adopts the Shapiro–Wilk test, and the 80%/80% rule was used for statistical analysis. Finally, we got five common frequencies of electromagnetic interference generated by the converter (electric field dB μ V/m). The CH4 sensor and other sensors work near these five dominant frequencies, which may affect the normal operation of the sensor and cause alarm. The test and analysis method proposed in this paper can be used to obtain the characteristic parameters of the converter electromagnetic disturbance, which can be used as a reference for the design of the immunity of sensors or control instruments.